Comparación de dos técnicas in vitro e in situ para estimar la digestibilidad verdadera en varios forrajes tropicales - Giraldo, Luis; Gutiérrez, Lina A.; Rúa, Claudia (Revista Colombiana de Ciencias Pecuarias, 2016)
Resumen Los estimados de digestibilidad in vitro verdadera de la materia seca se compararon en cuatro forrajes de origen tropical usando el incubador ANKOM DaisyII y la técnica in situ o de la bolsa de nylon. Hubo diferencia significativa (p < 0.05) en la digestibilidad verdadera in vitro de la materia seca (DVIVMS) entre los forrajes angleton, kikuyo y San Joaquín. No hubo diferencias significativas entre repeticiones (p > 0.05) para los distintos forrajes. La correlación entre la DVIVMS y la degradabilidad verdadera in situ de la materia seca (DVISMS), fue significativa y alta (p < 0.01, R² = 0.95) para los cuatro forrajes evaluados. Fue posible predecir la degradabilidad verdadera in situ de la materia seca con base en la digestibilidad verdadera in vitro de la materia seca mediante la ecuación: DVISMS = 6.16 + 0.87 * DVIVMS (p < 0.01, R2 = 0.95). Los resultados obtenidos, permiten confirmar que la técnica in vitro para estimar la digestibilidad verdadera utilizando el incubador DaisyII es confiable, rápida, precisa y sencilla, en comparación con el método in vivo utilizando la degradabilidad ruminal in situ o de la bolsa de nylon. Summary This study was conducted to evaluate the new in vitro system, DaisyII® and to compare its feasibility to determinate dry matter (DM) true digestibility in ruminant tropical forages as compared with the in situ (nylon bag) technique. Results from the DaisyII® incubator were compared to those obtained by traditional in situ (nylon bag technique) method. Four different forages were tested. Samples from each forage were (nylon bag technique) method. Four different forages were tested. Samples from each forage were Four different forages were tested. Samples from each forage were incubated (in situ) in the rumen of two bovines (incubation time: 48 h) or inserted (in vitro) into four different digestion jars that were placed into a DaisyII® incubator for 48h. The variability (coefficient of variation, CV) of the in vitro measurements (among jar repeatability) was low. The Daisy II® values were significantly higher than the degradability values as measured by the in situ method. When in vitro true dry matter digestibility (IVTDMD) obtained from in situ true dry matter digestibility (ISTDMD) was plotted against the Daisy II® data, the following linear equation was achieved. The degradability of dry matter obtained in situ (Y, true) and in vitro by DaisyII® (X, true after 48 h of incubation) were highly correlated (p < 0.01) and the regression equation was: Y = 6.16 + 0.87X, (R² = 0.95, p < 0.01). The DaisyII® incubator produces repeatable in vitro the dry matter degradability data which are highly related to those obtainable with the reference in situ procedure.